Perancangan Model Pertanian Terpadu Tanaman-Ternak dan Tanaman-Ikan di Perkampungan Teknologi Telo, Riau - ,, Suwarto; Aryanto, Agustinus Tri; Effendi, Irzal (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTThe Telo Technology Village of Bangkinang Seberang, Kampar, Riau was built on reclaimed land of C-mining excavation. On this land will be settled a number of farmer households pursue an area of 2,000 m2 in each. They should be able to maximize the land use to meet family needs adequately. In order to develop integrated farming system composed of crop, livestock, and fish productions, data were collected through interviews and literature. This study was conducted from February to July 2013. Models of integrated farming were designed and evaluated for its feasibility ecologically and economically using dynamic model Stella 9.2. Based on the models, integrated farming of spinach-kangkong-chili, cattle-laying ducks and Thai catfish-Tilapia fish will be able to provide an adequate income. Therefore area of 2,000 m2 is feasible for integrated farming, settlements and other households activities.Keywords: high mapping layer, LEISA, nutrient cycle